High secure buffer based physical unclonable functions (PUF’s) for device authentication - Sadulla Shaik; Anil Kumar Kurra; A. Surendar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Physical Unclonable Function (PUF) is fast growing technology which utilizes the statistical variability of the manufacture variations acts as a finger print to the each device. It can be widely used in security applications such as device authentication, key generation and Intellectual Property (IP) protection. Due to the simplicity and low cost arbiter delay based PUFs have been mostly used as a cryptographic key in Internet of Things (IoT) devices. As conventional arbiter PUFs are suffers from less uniqueness and reliability. This paper provides designing of new buffer based arbiter PUF. It has been demonstrated that experimental results of new buffer based arbiter PUF shows the considerable improvement in the uniqueness and reliability of the proposed design and the Monte-Carlo analysis applied for delay variability of the PUFs.